2019
DOI: 10.1590/s2175-97902019000217615
|View full text |Cite
|
Sign up to set email alerts
|

The anti-obesity potential of Ilex paraguariensis: results from a meta-analysis

Abstract: The dried leaves of Ilex paraguariensis, also known as yerba mate or chimarrão, are used to produce infusions consumed by over 1 million people worldwide, being a traditional drink in several South American countries, particularly, Argentina, Brazil, Uruguay, and Paraguay. The positive effects of I. paraguariensis in obesity have been described and observed in some clinical trials both in animals and in humans. The main goal of this work was to perform a systematic review, complying with the PRISMA (Preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…According to some papers, yerba mate may be used to reduce body weight due to its high content of caffeoylquinic acids [45,46]. Despite a lower amount of hydroxycinnamic derivates, European species may potentially be used for this purpose due to the relatively high amount of chlorogenic acids [47], absence of methylxanthines and ease of cultivation.…”
Section: Potential Utilisation Of Ilex Spp In Obesity Digestive Problems and Food Industrymentioning
confidence: 99%
“…According to some papers, yerba mate may be used to reduce body weight due to its high content of caffeoylquinic acids [45,46]. Despite a lower amount of hydroxycinnamic derivates, European species may potentially be used for this purpose due to the relatively high amount of chlorogenic acids [47], absence of methylxanthines and ease of cultivation.…”
Section: Potential Utilisation Of Ilex Spp In Obesity Digestive Problems and Food Industrymentioning
confidence: 99%
“…The positive effect of the chronic consumption of YM was probably through increase in both accelerated lipid mobilization and thermogenesis. Anti-obesity, lipid oxidation and thermogenesis effects of YM have been well documented in recent studies [3], [4], [7], [8], [18], [19]. Surprisingly, the most body weight loss was found in the YM-treated sedentary groups, indicating greater lipid mobilization and thermogenesis potential than that from training plus YM consumption.…”
Section: Resultsmentioning
confidence: 86%
“…Experimental studies targeting the effects of YM on the lipid and carbohydrate metabolism of adipose and musculoskeletal tissues have been steadily increasing for over a decade [2], [3]. A systematic review indicated positive effects on decreasing of both waist circumference and body weight, suggesting an anti-obesity potential [4]. A study carried out with sedentary healthy volunteers did not identify any influence on blood total CPK [5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, researches have shown that the consumption of yerba mate can be an interesting approach in the treatment of obesity. The mate extract has shown to modulate the expression of genes that were altered in obese patients, restoring their normal levels of expression (Kim, Ko, Storni, Song, & Cho, 2012; Luís, Domingues, & Amaral, 2019). A study carried out on the incidence of chronic diseases in postmenopausal women ( n = 95) demonstrated that after consuming 1 L/day of yerba mate infusion, the risk of dyslipidemia, hypertension, and coronary disease was reduced by 42%, 47.1%, and 100%, respectively (da Veiga, Bringhenti, Copes, et al, 2018; Schinella, Fantinelli, & Mosca, 2005).…”
Section: Chemical Composition Therapeutic and Nutraceutical Studies W...mentioning
confidence: 99%